2018
DOI: 10.1002/bit.26870
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of unprimed and dexamethasone‐primed nonviral gene delivery to human mesenchymal stem cells

Abstract: Human mesenchymal stem cells (hMSCs) are under intense study for applications of cell and gene therapeutics because of their unique immunomodulatory and regenerative properties. Safe and efficient genetic modification of hMSCs could increase their clinical potential by allowing functional expression of therapeutic transgenes or control over behavior and differentiation. Viral gene delivery is efficient, but suffers from safety issues, while nonviral methods are safe, but highly inefficient, especially in hMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 81 publications
(143 reference statements)
5
28
0
Order By: Relevance
“…An efficient nonviral gene delivery system for ex vivo genetic modification of clinically relevant hMSCs is lacking, however, our lab has previously demonstrated that pharmacological priming, or the addition of compounds to the culture media to modulate the cellular response to transfection, is a simple and effective method to enhance transfection in multiple cell types [15][16][17][23][24][25][26]. The idea of priming was developed after our studies using microarray analysis of transfected versus treated, but untransfected cells, where differentially expressed endogenous genes were identified between each condition in HEK 293 T cells and the expression of these identified genes were perturbed pharmacologically (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An efficient nonviral gene delivery system for ex vivo genetic modification of clinically relevant hMSCs is lacking, however, our lab has previously demonstrated that pharmacological priming, or the addition of compounds to the culture media to modulate the cellular response to transfection, is a simple and effective method to enhance transfection in multiple cell types [15][16][17][23][24][25][26]. The idea of priming was developed after our studies using microarray analysis of transfected versus treated, but untransfected cells, where differentially expressed endogenous genes were identified between each condition in HEK 293 T cells and the expression of these identified genes were perturbed pharmacologically (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to improving gene delivery to hMSCs is the idea of priming, where a compound is added to cultured cells to modulate the cellular response to nonviral gene delivery. Our lab has demonstrated that an antiinflammatory glucocorticoid drug, dexamethasone, can prime transfection to hMSCs from multiple donors and tissue sources by simple supplementation to the culture media 0-30 min prior to transfection [15,16]. With dexamethasone priming, we showed an increase in transgenic luciferase activity by 10-to 15-fold and an increase in the proportion of hMSCs expressing transgenic enhanced green fluorescent protein (EGFP) (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticosteroids are an efficient and widely used treatment for allergic respiratory diseases and are therefore considered anti‐allergic drugs . Low doses can stimulate the production of OPG and cause disassembly of cytoskeletal actin fibers present in clear and sealing zones of osteoclasts, which may interfere with the resorption process . Quercetin, a natural flavonoid, inhibits the release of histamine and leukotrienes and is also considered an anti‐allergic drug .…”
Section: Introductionmentioning
confidence: 99%